Small‐scale species distribution model identifies restricted breeding habitat for an endemic island bird. (6th May 2021) - Segal, R. D.; Massaro, M.; Carlile, N.; Whitsed, R.
Abstract: Mapped geographical distributions of many birds are an overestimation of their true range and this overestimation is particularly high for threatened species. Due to their restricted ranges, specialized habitats and inability to relocate to other areas, island birds are particularly vulnerable to anthropogenic effects on their habitats, but few studies have investigated the suitability of remaining habitat for species restricted to small oceanic islands. Here, we developed a fine‐scale species distribution model to investigate the breeding habitat of the Lord Howe currawong Strepera graculina crissalis . Using 73 nest locations as occurrence records, we found that currawongs nest preferentially near creek lines at lower elevations in the forested areas of the island (maximum elevation of 120 m). Habitat suitability decreased rapidly as the distance to creeks increased, indicating that many forested areas far from a creek line were unsuitable habitat for nesting currawongs. Using a combination of Thiessen polygons and suitable habitat to define territory boundaries, we estimated the average territory size to range between 2.48 ha and 5.23 ha. Using a conservative threshold, our model identified 195 ha of Lord Howe Island's land area as highly suitable nesting habitat for the Lord Howe currawong, while using a less conservative threshold identified a further 246 ha as medium suitable habitat (441 ha total). Hence, we estimated that the island can support a maximum number of 84 breeding territories. This study shows that the Lord Howe currawong has a narrower ecological niche than was expected, lowering the carrying capacity for this species on the island. As birds on remote islands are often unable to relocate to other suitable areas, it is important to determine the remaining habitat to ensure the continued persistence and conservation of threatened island species. Abstract : Due to their restricted ranges, specialised habitats, and inability to relocate to other areas, island birds are particularly vulnerable to anthropogenic effects on their habitats, but few studies have investigated the suitability of remaining habitat for species restricted to small oceanic islands. We developed a fine‐scale species distribution model (SDM) to investigate the breeding habitat of the Lord Howe currawong Strepera graculina crissalis . This study shows that the Lord Howe currawong has a narrower ecological niche than was expected, lowering the carrying capacity for this species on the island.